The impact of Kiyoshi Itô´s stochastic calculus of financial economics (2016)
We discuss the direct or indirect incorporation into financial economics of Kiyoshi Itô´s work on stochastic calculus, particularly the Itô formula, the relevance of his findings for option pricing theory and the way his work has been used to find a unique option pricing function in a competitive and non-arbitrage market. On that basis, we discuss how the option pricing theory may be linked with the general equilibrium theory and other aspects of conventional economics, and finally, Itô’s role in econophysics.